Development of a problem-based learning biology learning website on the body defense system material - Zakiatul Masithoh; Zulfiani Zulfiani; Solihin Solihin (STKIP Persada Khatulistiwa Sintang, 2026)
The development of digital technology encourages the use of learning media that increase student engagement and problem-solving abilities. However, biology learning about the body's defense system material is still dominated by conventional methods, making it less than optimal in training these abilities. This study aims to develop and test the feasibility of a WordPress-based Problem-Based Learning (PBL) biology learning website. The study employed the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Research subjects involved media experts, material experts, biology teachers, grade XI students, and teachers from MAN in Bekasi City. Data were collected through validation questionnaires and response questionnaires. The research results show that the learning website has very high validity with percentages of 88.8% (media expert) and 92% (material expert), very high practicality with percentages of 90% (teachers) and 94.7% (students), and 89% effectiveness in the effective category. The PBL-based biology learning website is declared suitable for use as a learning medium on body defense system material.